Sepsis Course and Outcome Depends on the Genetic Variant in the 3`-Region of Aquaporin 4 Gene AQP4 and Comorbidities - A. G. Chumachenko; E. K. Grigoriev; R. A. Cherpakov; I. N. Tyurin; V. M. Pisarev (Общая реаниматология, 2023)
Aquaporins 4 and 5 are proteins that form water channels in the cell membrane, participate in the transfer and migration of immune cells, being expressed on many cell types including CNS astrocytes, kidney cells, lungs, and the immune system. We have previously shown that AQP5 genetic polymorphism is associated with different outcomes of abdominal sepsis. Since another common aquaporin protein, AQP4, is also expressed on the surface of immunocompetent cells, determining cell motility, it was suggested that AQP4 may also be important in the pathogenesis of sepsis, and that AQP4 polymorphism may predetermine sepsis severity and outcome. AQP4 rs1058427 genetic polymorphism has not been studied earlier. The aim of the study was to determine the effects of region 3` polymorphism in the AQP4 gene on the clinical course and outcome of sepsis.Materials and methods. The prospective study included 290 ICU patients from three clinical hospitals in Moscow aged 18–75 years with clinical signs of sepsis (SEPSIS-3, 2016).Results. It was found that the minor T allele of the AQP4 rs1058427 gene provides strong protection against septic shock, as among GG genotype carriers septic shock developed in 66%, but in presence of the minor T allele dropped to half of cases (P=0.009, Fisher’s exact test, OR=1.99, 95% CI: 1.12–3.55, N=290). There was a significant association between AQP4 rs1058427 genetic polymorphism and 30-day hospital mortality in a subgroup of patients with more severe organ dysfunction and higher comorbidity burden (cardiovascular diseases, type II diabetes mellitus) requiring extracorporeal treatment modalities and ventilator support for 5 or more days (N=66). Carriers of the minor T allele showed better survival rates as compared AQP4 rs1058427 GG genotype carriers (5 deaths out of 10 and 47 deaths out of 56, respectively, P=0.003, Fisher’s exact test, N=66, OR=5.22, 95% CI: 1.25–21.82, P=0.009, log-rank criterion).Conclusion. The minor AQP4 rs1058427 T allele is associated with protection against septic shock and better survival in sepsis in a group of ICU patients with high comorbidity burden requiring extracorporeal life support interventions.